2021
DOI: 10.1002/sd.2260
|View full text |Cite
|
Sign up to set email alerts
|

Evolution, trends and future research lines in corporate social responsibility and tourism: A bibliometric analysis and science mapping

Abstract: Corporate social responsibility (CSR) has become a topic of growing interest in countless areas, and the number of studies focused on researching different CSR aspects is increasing. Nevertheless, this type of research within the tourism sector is less developed compared to other fields. Consequently, a significant research opportunity in the tourism industry has been detected. Therefore, this study uses the SciMAT software to analyze 1800 articles published on CSR within the tourism field through the co‐word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 121 publications
1
14
0
1
Order By: Relevance
“…Using such methodologies allows for the assessment of citations, field growth, conceptual structure, leading authors, trends, and scientific communities [ 36 ]. Bibliometrics has proven to be a valuable tool for providing a comprehensive overview of journals [ 5 , 37 ] or research fields [ 11 , 31 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using such methodologies allows for the assessment of citations, field growth, conceptual structure, leading authors, trends, and scientific communities [ 36 ]. Bibliometrics has proven to be a valuable tool for providing a comprehensive overview of journals [ 5 , 37 ] or research fields [ 11 , 31 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Future research should focus on investigating corporate social responsibility in tourism and hospitality (Madanaguli et al, 2021 ; Peña‐Miranda et al, 2021 ; Sánchez‐Camacho et al, 2021 ). Future scholars could also investigate the role of corporate social responsibility in the hotel industry in achieving sustainable development goals.…”
Section: Post‐covid‐19 Agenda and Call For Future Researchmentioning
confidence: 99%
“…The literature on the topic of tourism sustainability has grown significantly in recent years, as evidenced by a search for articles utilizing the keywords "tourism", "sustainability" and "bibliometric analysis" in Scopus and the Web of Science (WoS) databases. As of 28 January 2023, a total of 53 articles were found that addressed various aspects of tourism sustainability, such as over-tourism [2], corporate social responsibility [3,4], community participation [5], sharing economy [6], sustainability education [7], sustainability in hospitality and tourism [8], tourism management and marketing [9], and tourism entrepreneurship [10,11]. This indicates a growing interest in the field of tourism sustainability and highlights the need for further examination of the literature in this area.…”
Section: Literature Reviewmentioning
confidence: 99%